Language Dynamics in EFL Classrooms: Insights from Islamic Junior High School Teachers in Jambi on the Use of Bahasa Indonesia and Arabic - Andy Basoka Iskandar; Failasofah (EduInovasi: Journal of Basic Educational Studies, 2025)
This study explored the use of Bahasa Indonesia and Arabic in teaching English as a Foreign Language (EFL) at Islamic junior high schools in Jambi, Indonesia. The research aimed to understand the dynamics of using these languages in EFL classrooms and to gather teachers' perspectives on this practice. Through semi-structured interviews and classroom observations, the study identified the benefits, challenges, and impacts of incorporating Bahasa Indonesia and Arabic into EFL instruction. The findings suggested that strategic use of these languages can enhance comprehension, classroom management, and cultural relevance, but also presented challenges in balancing language use and meeting institutional and community expectations.